2020
DOI: 10.1128/jvi.01337-19
|View full text |Cite
|
Sign up to set email alerts
|

CpG Dinucleotides Inhibit HIV-1 Replication through Zinc Finger Antiviral Protein (ZAP)-Dependent and -Independent Mechanisms

Abstract: CpG dinucleotides are suppressed in the genomes of many vertebrate RNA viruses, including HIV-1. The cellular antiviral protein ZAP (zinc finger antiviral protein) binds CpGs and inhibits HIV-1 replication when CpGs are introduced into the viral genome. However, it is not known if ZAP-mediated restriction is the only mechanism driving CpG suppression. To determine how CpG dinucleotides affect HIV-1 replication, we increased their abundance in multiple regions of the viral genome and analyzed the effect on RNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
102
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(106 citation statements)
references
References 83 publications
4
102
0
Order By: Relevance
“…(1) Our results for A → G and T → C mutations are very similar, if this was due to a mutation rate effect, it would have to have the same effect on both of these mutation types. (2) Our results are consistent with results from epidemiological studies on polio (Stern et al 2017) and in vitro studies on HIV (Takata et al 2017;Ficarelli et al 2019). Future studies will hopefully measure viral mutation rates with more precision.…”
Section: Limitations and Future Studiessupporting
confidence: 84%
See 1 more Smart Citation
“…(1) Our results for A → G and T → C mutations are very similar, if this was due to a mutation rate effect, it would have to have the same effect on both of these mutation types. (2) Our results are consistent with results from epidemiological studies on polio (Stern et al 2017) and in vitro studies on HIV (Takata et al 2017;Ficarelli et al 2019). Future studies will hopefully measure viral mutation rates with more precision.…”
Section: Limitations and Future Studiessupporting
confidence: 84%
“…It is not entirely clear why CpG sites are costly, but it is likely, at least in part, because the mammalian immune system uses CpG sites to recognize foreign genetic material (Murphy and Weaver 2016). Recently it was shown that ZAP proteins, which inhibit the proliferation of most RNA viruses, are more effective when the CpG sites were common (Takata et al 2017;Ficarelli et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The codon pair bias attenuation effect has more recently been shown to be largely owing to increased CpG content (Tulloch, et al 2014;Gaunt, et al 2016). This is very likely to relate to the activity of the human Zinc Antiviral Protein (ZAP) as this targets transcripts with high CpG content (Takata, et al 2017;Ficarelli, et al 2020), although it is by no means the only antiviral peptide ( Supplementary Table 1). As might be expected, ZAP is under positive selection owing to host-parasite coevolution (Kerns, et al 2008).…”
Section: Generalization Of Resultsmentioning
confidence: 99%
“…ZAP-L has been reported to represent the most antivirally active isoform but is not significantly upregulated by IFN, while the shorter ZAP-S also exerts antiviral activity and is IFN-inducible but may actually act as a negative feedback regulator of the interferon response [95]. Depletion of ZAP reduced the inhibitory effect of type I IFN on CpG-enriched HIV-1, suggesting that this factor contributes to the antiviral IFN response [96]. Importantly, ZAP needs cofactors to exert antiviral activity.…”
Section: Cellular Factors Targeting Hiv-1 Rna Transcriptsmentioning
confidence: 99%
“…Notably, the inhibitory effect of ZAP on HIV-1 and other primate lentiviruses is not only determined by CpG frequency. Using different approaches, i.e., artificial CpG-enrichment in specific regions of the HIV-1 genome [96] and analyses of a large panel of primary infectious molecular clones of HIV-1 [100], two recent studies showed that the CpG frequency in first part of the viral env gene, rather than the overall content, determines ZAP sensitivity. The latter study also showed that the genomes of different primate lentiviruses differ substantially in CpG frequencies, and that the magnitude of suppression does not correlate with ZAP sensitivity, suggesting possible viral evasion or counteraction mechanisms.…”
Section: Cellular Factors Targeting Hiv-1 Rna Transcriptsmentioning
confidence: 99%